Computer simulations for the extended Hubbard model utilizing Nonextensive Statistical Mechanics - R. Navarro, F. A. (2011)
We study a system formed by M dimers through half-filled two-site Hubbard model, with two electrons. Our approach use the third version of Nonextensive Statistical Mechanics as tool for calculating thermodynamic and magnetic parameters such as entropy, internal energy, magnetization and specific heat. In the computer simulations, we vary the q entropic index values between 1 and 2, such that, q = 1.0, 1.4, 1.7 and 2.0. These values are interesting to study small magnetic systems. We find the critical temperature regions in simulations with the simple Hubbard model, i.e. without the intersite interaction. For other side, adding this additional term, we notice an enlargement and shifting of the thermodynamic parameters comparing with the obtained from simple Hubbard model; even more, we found in some cases the absence of the critical temperature regions.